1999
DOI: 10.1212/wnl.52.7.1384
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proton MRS predicts outcome after traumatic brain injury

Abstract: 1H-MRS provides a rapid, noninvasive tool to assess the extent of diffuse injury after head trauma, a component of injury that may be the most critical factor in evaluating resultant neuropsychological dysfunction. 1H-MRS can be added to conventional MR examinations with minimal additional time, and may prove useful in assessing injury severity, guiding patient care, and predicting patient outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
104
1
6

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(118 citation statements)
references
References 30 publications
7
104
1
6
Order By: Relevance
“…This was true for short echotime single-voxel spectra from normal-appearing OGM and POWM, as well as intermediate echo-time regional MRSI data. The findings from the current study are consistent with the literature on single-voxel spectra from normal-appearing brain and suggest that reduced levels of NAA measured relatively soon after a brain injury in both adults and children is associated with long-term neurologic and cognitive outcome (3,34,35). Studies using MRSI in children also showed NAA/Cre reductions early after injury (10) as well as decreased NAA/Cho ratios up to three years post injury (36).…”
Section: Discussionsupporting
confidence: 88%
“…This was true for short echotime single-voxel spectra from normal-appearing OGM and POWM, as well as intermediate echo-time regional MRSI data. The findings from the current study are consistent with the literature on single-voxel spectra from normal-appearing brain and suggest that reduced levels of NAA measured relatively soon after a brain injury in both adults and children is associated with long-term neurologic and cognitive outcome (3,34,35). Studies using MRSI in children also showed NAA/Cre reductions early after injury (10) as well as decreased NAA/Cho ratios up to three years post injury (36).…”
Section: Discussionsupporting
confidence: 88%
“…In general, however, we found that pooled mean NAA/Cr and NAA/Cho ratios decreased after injury and remained low in patients with poor outcomes. This is in agreement with previous studies (5,11). The changes seen in this study are attributed primarily to NAA decreases that were observed in the spectra and because quantitative Cr levels measured in the same cohort of patients from occipital gray matter and parietal white matter were not significantly different between patients with good and poor outcomes or controls (8).…”
Section: Pooled Measurementssupporting
confidence: 93%
“…The changes seen in this study are attributed primarily to NAA decreases that were observed in the spectra and because quantitative Cr levels measured in the same cohort of patients from occipital gray matter and parietal white matter were not significantly different between patients with good and poor outcomes or controls (8). Decreases in NAA could represent either neuronal loss or neuronal dysfunction, since NAA has been shown to recover after restoration of energy failure (5,18). It has been postulated that a temporary drop in NAA following brain injury may be caused by accelerated lipid synthesis involved in myelin repair or because NAA provides a temporary source of cellular energy locally at the site of axonal injury, thus producing a transient drop that could precede any loss of NAA as a result of axonal death (10).…”
Section: Pooled Measurementsmentioning
confidence: 56%
See 1 more Smart Citation
“…Most (but not all) of these studies have demonstrated decreased absolute NAA and NAA/Cr ratios and decreased NAA to correlate with poor outcomes. 54,67, [84][85][86] Decreased NAA/Cr ratios have been detected in the splenium of the corpus callosum and, to a lesser, extent in the lobar white matter. 80 In pediatric patients with accidental and nonaccidental TBI, MR spectroscopy has shown potential for providing early prognostic information regarding clinical outcomes.…”
Section: Mr Spectroscopymentioning
confidence: 99%